PENGARUH EKUITAS MEREK, BRAND IMAGE DAN LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK IPHONE - Nursyah Dila (FKIP Unswagati, 2024)
This research is motivated by the perception of the majority of students, especially students of the Malikussaleh University Management Study Program, that when they own or use a device with the iPhone brand, it has a certain prestige. The iPhone is not only used as a communication tool but also used as a lifestyle symbol. So based on this, this research aims to obtain a systematic picture of the variables of service quality, brand value and lifestyle as independent variables and purchasing decisions as the dependent variable. This research is quantitative research with the research sample being students from the Malikussaleh University Management Study Program with a total of 150 students. The analysis used in this research is alternating regression analysis. The results of this research are that there is no simultaneous relationship between Product Quality, Brand Equity and Lifestyle.